Investor Sentiment, Overconfidence, and Market Volatility: Insights from Global Stock Exchanges - Lina Maretta; Jonas Redwood (Journal of Management and Informatics, 2025)
The increasing turbulence in global stock markets has sparked growing attention toward the role of behavioral factors in shaping investor decisions. Traditional financial theories often assume rationality; however, evidence shows that psychological biases, such as investor sentiment and overconfidence, frequently disrupt market efficiency. This study investigates how investor sentiment and overconfidence bias influence market volatility across international stock exchanges, addressing gaps in prior research that often examine these factors in isolation. A quantitative research design was employed, combining a behavioral survey of active investors with secondary data from global stock indices from 2018 to 2023. The behavioral survey captured self-reported sentiment and overconfidence, while the secondary dataset provided market-level volatility indicators. Structural equation modeling (SEM) was applied to test the hypothesized relationships, with robustness checks conducted via regression analysis. Instrument reliability and validity were confirmed, ensuring measurement consistency. The findings reveal that both investor sentiment and overconfidence bias significantly drive fluctuations in market volatility, with overconfidence exerting a more substantial amplifying effect. Interactions between sentiment and overconfidence further intensify volatility during periods of global uncertainty, illustrating the complex and nonlinear nature of behavioral influences. These results align with behavioral finance theory, which posits that markets are not purely efficient but are shaped by human cognition and emotion. The study provides empirical insights from a cross-market perspective, bridging behavioral finance with international management research, and offers practical guidance for policymakers, regulators, and financial advisors in managing behavioral risks to enhance global market stability.